2021
DOI: 10.1186/s13018-021-02658-1
|View full text |Cite
|
Sign up to set email alerts
|

Potential genes and pathways associated with heterotopic ossification derived from analyses of gene expression profiles

Abstract: Background Heterotopic ossification (HO) represents pathological lesions that refer to the development of heterotopic bone in extraskeletal tissues around joints. This study investigates the genetic characteristics of bone marrow mesenchymal stem cells (BMSCs) from HO tissues and explores the potential pathways involved in this ailment. Methods Gene expression profiles (GSE94683) were obtained from the Gene Expression Omnibus (GEO), including 9 nor… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 50 publications
0
5
0
Order By: Relevance
“…Proteins isolated from the EVs of patients in the fracture group showed that a sizeable ratio (57.5%) was related to the VEGF/VEGFR and PDGF receptor signaling network and the IGF-1 pathway, while 21.3% of isolated proteins were involved in the Wnt signaling network. To further compare the processes of fracture healing and HO that is evident in FOP, we analysed the Ephrin-B pathway that is enriched in HO and has important implications in it, such as enhancing endochondral ossification in fracture repair ( Arthur et al, 2013 ; Yang et al, 2021 ). Ephrin-B activation was identified in the FOP and fracture groups, but not in the control group.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Proteins isolated from the EVs of patients in the fracture group showed that a sizeable ratio (57.5%) was related to the VEGF/VEGFR and PDGF receptor signaling network and the IGF-1 pathway, while 21.3% of isolated proteins were involved in the Wnt signaling network. To further compare the processes of fracture healing and HO that is evident in FOP, we analysed the Ephrin-B pathway that is enriched in HO and has important implications in it, such as enhancing endochondral ossification in fracture repair ( Arthur et al, 2013 ; Yang et al, 2021 ). Ephrin-B activation was identified in the FOP and fracture groups, but not in the control group.…”
Section: Resultsmentioning
confidence: 99%
“…Osteogenic and chondrogenic differentiation of MSCs is one of the factors necessary for the occurrence and development of HO, FOP being no exception ( Huang et al, 2021 ). Not much is known about the connection between Ephrin signaling and HO, but the Ephrin-B3 gene has previously been found to be intensively enriched in HO by gene expression analysis ( Matsuo et al, 2019 ; Yang et al, 2021 ). Our results show that the FOP flare-up group showed expression of most Ephrin-B associated proteins, compared to other analysed groups.…”
Section: Discussionmentioning
confidence: 99%
“…Hirata et al discovered that PMEPA1-deficient mice exhibit increased bone volume and decreased bone resorption activity, proton secretion from osteoclasts significantly decreased in PMEPA1 mutant osteoclasts ( Hirata et al, 2021 ). In an analysis of gene expression in heterotopic ossification, Yang et al reported a downregulation of UNC5C gene expression which might be associated with heterotopic ossification ( Yang et al, 2021 ). Estrogens are important for bone metabolism via a variety of mechanisms in osteoblasts, osteocytes, osteoclasts, immune cells, and other cells to maintain bone mineral density ( Khalid and Krum, 2016 ).…”
Section: Discussionmentioning
confidence: 99%
“…In this study, statistically significant upregulation of Fbn2 at the transcriptional level was demonstrated in the physis tissues of rats exposed to 0.05 mg·kg −1 ·day −1 of BPA, which may indicate that BPA disturbs this pace. There is evidence linking ADAMTS16 to heterotopic ossification, osteoarthritis, bone mineral density, and bone fragility (Yang et al, 2021b; Kevorkian et al, 2004; Hsu et al, 2019). Neonatal BPA contamination leads to a higher Adamts16 mRNA expression, similar to the osteoarthritis state (Kevorkian et al, 2004).…”
Section: Discussionmentioning
confidence: 99%